Effects of strength training on squat and sprint performance in soccer players - Styles, W. J.; Matthews, M. J.; Comfort, P. (The Journal of Strength and Conditioning Research, 2016)
Researchers have demonstrated that increases in strength result in increases in athletic performance, although the development of strength is still neglected in some sports. Our aim was to determine whether a simple in-season strength training program would result in increases in maximal squat strength and short sprint performance, in professional soccer players. Professional soccer players (n = 17, age = 18.3 ± 1.2 years, height = 1.79 ± 0.06 m, body mass [BM] = 75.5 ± 6.1 kg) completed 1 repetition maximum (1RM) back squat and sprint tests (5, 10, and 20 m) before and after a 6-week (×2 week) in-season strength training (85-90% 1RM) intervention. Strength training resulted in significant improvements in absolute and relative strength (before = 125.4 ± 13.8 kg, after = 149.3 ± 16.2 kg, p = 0.001, Cohen's d = 0.62; 1RM/BM before: 1.66 ± 0.24 kg/kg, after = 1.96 ± 0.29 kg/kg, p = 0.001, Cohen's d = 0.45; respectively). Similarly, there were small yet significant improvements in sprint performance over 5 m (before = 1.11 ± 0.04 seconds, after = 1.05 ± 0.05 seconds, p = 0.001, Cohen's d = 0.55), 10 m (before = 1.83 ± 0.05 seconds, after = 1.78 ± 0.05 seconds, p = 0.001, Cohen's d = 0.45), and 20 m (before = 3.09 ± 0.07 seconds, after = 3.05 ± 0.05 seconds, p = 0.001, Cohen's d = 0.31). Changes in maximal squat strength seem to be reflected in improvements in short sprint performance highlighting the importance of developing maximal strength to improve short sprint performance. Moreover, this demonstrates that these improvements can be achieved during the competitive season in professional soccer players.